Incidence of Stereo Blindness in a Recent VR Distance Perception User Study - Wiebrands, M.; Woods, Andrew; Riddell, Hugh (2023)
Estimates of stereo-blindness, the inability to see in 3D using stereopsis, often sit in the 5-10% range. At the Curtin University HIVE visualisation facility, we regularly show stereoscopic content. During those demonstrations we routinely show a test random dot stereogram and it has been our casual observation that the incidence of stereo-blindness amongst visitors has been much lower than the 5-10% figure, perhaps as low as 2%. Our thought was that perhaps eye care has improved since the time that the original stereo-blindness studies were performed. A virtual reality (VR) based user study was recently run in the HIVE, as part of a PhD project, with an aim to study distance perception in underwater virtual heritage experiences. Distance perception is facilitated by a range of visual cues, including stereoscopic vision, and as a result we formally screened all participants for stereo-blindness. Using a standardised stereo test, we found approximately 5% of participants reported as stereo blind.